Perjuangan Tokoh Perempuan dalam Cerita Pendek â€œAirâ€ Karya Djenar Maesa Ayu - Asriningsih, Nuraini; Turahmat, Turahmat (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This short "water" story by Djenar Maesa Ayu is the background of the life of a woman who struggled and worked hard to raise her child, without getting the responsibility of the prospective baby's father. The problem of this research is the struggle of female leaders. This study aims to describe the struggles of female leaders in the short story Air by Djenar Maesa Ayu. This study uses a feminist literary criticism approach. The method used is descriptive qualitative. The data source is Air's short story by Djenar Maesa Ayu. The technique used is the data validation technique. This research draws conclusions about the struggles of female leaders. Keywords: the struggle of female leaders; short stories.